ESTUDO LONGITUDINAL DE FATORES QUE AFETAM O RISCO DE FRATURA POR ESTRESSE EM DUAS POPULAÇÕES DE COLEGIAIS DO SEXO FEMININO - Barfield, William R.; Otteni, Jack F.; McBryde, Angus; Carter, John S.; Nietert, Paul J. (Journal of Exercise and Sport Sciences, 2005)
Objetivos: As fraturas por estresse causam significante morbidade em mulheres. Diferenças no nível de atividades, valores hormonais e densidade mineral óssea (BMD) afetam diferentemente as taxas de fraturas por estresse. Os autores hipotetizaram que mulheres de um Colégio militar terão maior nível de atividade do que mulheres em colégios com um ambiente mais flexível, que correlacionará com mudanças nos valores hormonais, menor (BMD) e mais fraturas por estresse. Método: Nesse estudo prospectivo comparativo, 63 mulheres de duas Instituições (The Citadel: The Military College Of South Carolina And The College Of Cherleston) relataram detalhadamente suas atividades, dieta e lesões através de um questionário e tiveram sua BMB e os valores hormonais séricos medidos num intervalo de 06 meses, por um período de 2 anos; 38 sujeitos completaram o estudo. A análise estatística examinou diferenças e mudanças ao longo do tempo entre as duas amostras.Resultados: Uma fratura por estresse ocorreu em cada Instituição. As mulheres do Citadel tiveram maiores níveis de atividade, que as mulheres do College of Charleston no longo do estudo. As mulheres do Citadel tiveram menor nível de hormônio folículo estimulante, maior 17 Beta-Estradiol aos 24 meses e maior BMD na extremidade proximal femoral aos 18 meses da investigação (p< 0,05). Conclusões: Os valores séricos hormonais podem ser um indicador mais sensível de resposta ao nível da atividade física que o BMD dentro da amostra e duração deste estudo. Outros estudos são necessários para definir esta complexa interrelação. LONGITUDINAL STUDY OF FACTORS AFFECTING STRESS FRACTURE RISK IN TWO DISTINCT COLLEGE FEMALE POPULATIONS Abstract Objectives: Stress fractures cause significant morbidity in females. Differences in activity levels, hormone values, and bone mineral density (BMD) affect different rates of stress fracture. The authors hypothesized that females at a military college will have greater activity levels than females in a flexible college environment, which will correlate with greater changes in hormone values, lower BMD, and more stress fractures. Methods: In this prospective comparative study 63 females from two institutions (The Citadel: The Military College of South Carolina and the College of Charleston) self-reported on a detailed activity, diet, and injury questionnaire and had BMD and serum hormone values measured at 6- month intervals for a two year period; 38 completed the study. Statistical analysis was designed to examine differences and changes over time between the two samples. Results: One stress fracture occurred in each institution. Citadel females had higher activity levels than females at the College of Charleston throughout the study. Citadel females had lower follicle stimulating hormone levels at 24 months, greater 17 beta-estradiol at 24 months, and greater proximal femoral BMD at eighteen months (p<.05). Conclusions: Serum hormone values may be a more sensitive indicator of responses to activity level than BMD within the subject selection and duration of this study. Further studies are necessary to fully define this complicated interrelationship. Objectives: Stress fractures cause significant morbidity in females. Differences in activity levels, hormone values, and bone mineral density (BMD) affect different rates of stress fracture. The authors hypothesized that females at a military college will have greater activity levels than females in a flexible college environment, which will correlate with greater changes in hormone values, lower BMD, and more stress fractures. Methods: In this prospective comparative study 63 females from two institutions (The Citadel: The Military College of South Carolina and the College of Charleston) self-reported on a detailed activity, diet, and injury questionnaire and had BMD and serum hormone values measured at 6- month intervals for a two year period; 38 completed the study. Statistical analysis was designed to examine differences and changes over time between the two samples. Results: One stress fracture occurred in each institution. Citadel females had higher activity levels than females at the College of Charleston throughout the study. Citadel females had lower follicle stimulating hormone levels at 24 months, greater 17 beta-estradiol at 24 months, and greater proximal femoral BMD at eighteen months (p<.05). Conclusions: Serum hormone values may be a more sensitive indicator of responses to activity level than BMD within the subject selection and duration of this study. Further studies are necessary to fully define this complicated interrelationship.